Metodologi Pengajaran PAI dengan Metode Pembelajaran Quantum Learning di Madrasah Aliyah Negeri 1 Kabupaten Batang Hari - Asmadi, Asmadi; Adhiyah, Adhiyah; Ramadani, Anisa; Jannah, Nurjatul; Andriwidayan, Wahyu; Albasit, Ghofur Mualif (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2024)
This study explores the implementation and understanding of the quantum learning method in the teaching of Islamic Cultural History at Madrasah Aliyah Negeri (MAN) 1 Batang Hari. The research investigates the application of this method, the challenges encountered during its implementation, and the strategies employed to address these challenges. Using a qualitative research approach, data were collected from educators who served as the primary informants. The findings reveal that the application of quantum learning aligns with established guidelines and significantly enhances the learning process by incorporating diverse educational media to optimize student engagement and comprehension. This study concludes that the quantum learning method, when adapted effectively, can improve the quality of teaching Islamic Cultural History and offers practical insights into overcoming potential obstacles in its implementation.